The Use of Describing Picture Strategy to Improve Students’ Ability in Writing Descriptive Text - Elyas Ajunge (Graduate Program, University of Islam Malang, 2020)
This study aims to improve students’ ability in writing descriptive texts. The subjects of this study were eight grade students. Total of the students were 21. This study consisted of 2 cycles, each cycle consisting of 3 meetings. In the first cycle, the picture strategy procedures were (a) The researcher gave a picture to students, (b) the researcher asked students to write vocabularies of the picture (c) the researcher asked students to arrange vocabularies into sentences. However, steps above had not been successful to improve the students’ ability so the researcher improved steps in cycle 2 into (a) the researcher divided students into 7 groups with 3 members for each group, (b) the researcher gave the group picture, (b) The researcher asked students to discuss the picture, (c) The researcher asked students to write the vocabulary from the picture, (d) The researcher asked students to make a written description on each paper based on the written vocabulary. The steps improved in cycle 2 made students easy to write a description because they discussed the picture. Because the score in cycle 2 met the criteria, the researcher stopped the study.Arikunto. Suharsimi. 2006. Prosedur Penelitian suatu pendekatan Praktek. Jakarta: Reineka Cipta.Hornby. 2000. AS Oxford Advanced Learner’s Dictionary of Current English, 6th ed. Oxford: Oxford University Press.Nurgyantoro, Burhan. (2010). Penilaian Pembelajaran Bahasa Berbasis Kompetensi. (cetakanke-1). Yogyakarta: BPFE-YogyakartaRofi’uddin, Ahmad & Zuhdi, Darmiyati. 1999. Pendidikan Bahasa dan Sastra Indonesia di Kelas Tinggi. Jakarta: Dirjen Dikti.Setyadi, Bambang. Ag. 2006. Teaching English as a foreign language. Yogyakarta. Graha ilmu.